Alkalinity cycling and carbonate chemistry decoupling in seagrass mystify processes of acidification mitigation - Cale A. Miller (Nature Portfolio, 2021)
Abstract The adverse conditions of acidification on sensitive marine organisms have led to the investigation of bioremediation methods as a way to abate local acidification. This phytoremediation, by macrophytes, is expected to reduce the severity of acidification in nearshore habitats on short timescales. Characterizing the efficacy of phytoremediation can be challenging as residence time, tidal mixing, freshwater input, and a limited capacity to fully constrain the carbonate system can lead to erroneous conclusions. Here, we present in situ observations of carbonate chemistry relationships to seagrass habitats by comparing dense (DG), patchy (PG), and no grass (NG) Zostera marina pools in the high intertidal experiencing intermittent flooding. High-frequency measurements of pH, alkalinity (TA), and total-CO2 elucidate extreme diel cyclicity in all parameters. The DG pool displayed frequent decoupling between pH and aragonite saturation state (Ωarg) suggesting pH-based inferences of acidification remediation by seagrass can be misinterpreted as pH and Ωarg can be independent stressors for some bivalves. Estimates show the DG pool had an integrated ΔTA of 550 μmol kg−1 over a 12 h period, which is ~ 60% > the PG and NG pools. We conclude habitats with mixed photosynthesizers (i.e., PG pool) result in less decoupling between pH and Ωarg.